2017
DOI: 10.1186/s12989-017-0183-7
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and postnatal mothering by diesel exhaust PM2.5-exposed dams differentially program mouse energy metabolism

Abstract: BackgroundObesity is one of the leading threats to global public health. It is consequent to abnormal energy metabolism. Currently, it has been well established that maternal exposure to environmental stressors that cause inappropriate fetal development may have long-term adverse effects on offspring energy metabolism in an exposure timing-dependent manner, known as developmental programming of health and diseases paradigm. Rapidly increasing evidence has indicated that maternal exposure to ambient fine partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…Therefore, as per the DPoHaD paradigm, maternal exposure to ambient PM 2.5 is likely to be a risk factor for the DPoHaD. In agreement with this, we recently demonstrated that maternal exposure to diesel exhaust PM 2.5 (DEP, one of the major sources of ambient PM 2.5 in urban areas) persistently influences male offspring's development and increases their adulthood adiposity (6). As obesity is one of the major risk factors for diabetes, how maternal exposure to DEP influences offspring's glucose homeostasis has to be determined.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…Therefore, as per the DPoHaD paradigm, maternal exposure to ambient PM 2.5 is likely to be a risk factor for the DPoHaD. In agreement with this, we recently demonstrated that maternal exposure to diesel exhaust PM 2.5 (DEP, one of the major sources of ambient PM 2.5 in urban areas) persistently influences male offspring's development and increases their adulthood adiposity (6). As obesity is one of the major risk factors for diabetes, how maternal exposure to DEP influences offspring's glucose homeostasis has to be determined.…”
Section: Introductionsupporting
confidence: 62%
“…Prenatal exposure to DEP results in glucose intolerance in adult male offspring. We recently reported that dams' prenatal or postnatal exposure to DEP differentially programs mouse E74 PM2.5 EXPOSURE AND OFFSPRING ␤ CELL FUNCTION energy metabolism and adiposity in adulthood (6). As adiposity is well known to correlate to glucose homeostasis, we performed glucose homeostasis assessments on these adult male offspring.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following amplification, a dissociation curve analysis was performed to ensure purity of PCR product. The specific sense and antisense primers for tumor necrosis factor- , interleukin (IL)-6, , and glyceraldehyde 3-phosphate dehydrogenase (GAPDH) (the reference housekeeping gene) were previously described ( Chen et al. 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…An increasing number of studies in both human and animal models have shown that prenatal exposure to ambient fine particles is associated with a variety of abnormalities during foetal development, such as preterm birth, low birth weight and placental dysfunctions [1417]. Moreover, there is clear evidence that gestational exposure to pollutants can also have deleterious long term effects that mainly involve energy metabolism disorders [18, 19] and cardiac and respiratory dysfunctions [4, 20, 21]. We have previously reported that females exposed daily during pregnancy to DE particles at levels close to urban pollution evidenced foeto-placental disorders [14].…”
Section: Introductionmentioning
confidence: 99%